THE MOVEMENT STRUCTURE OF THE AJAAT TEMUAI DATAI DANCE OF DAYAK MUALANG TRIBE IN BELITANG HILIR DISTRICT SEKADAU REGENCY WEST KALIMATAN - Berlisia, Melisa; Istiandini, Winda; Tindarika, Regaria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The Ajaat Temuai Datai dance is one of the traditional dances owned by the Dayak Mualang tribe. It is necessary to know the structure of the movements in this dance because there are several changes that occur in the movements that make the Ajaat Temuai Datai dance lose its original movement identity. This study aims to describe the movement structure of the Ajaat Temuai Datai dance of the Dayak Mualang tribe in Belitang Hilir District, Sekadau Regency, West Kalimantan. The method used is a descriptive method with a qualitative research form and a choreographic approach. The technique to test the validity of the data used is the extension of observations and source triangulation. Based on the data analysis, it was concluded that the movement structure of the Ajaat Dance Temuai Datai of the Dayak Mualang Tribe in Belitang Hulu District, Sekadau Regency, West Kalimantan is as follows: there are six variations of motion consisting of Herding Meet, Ngelempai, Ngancau Tikai, Dara Kenyalang, Kesulang Inok, Kesulang Male, and closing with a meeting. The Ajaat Temuai Datai dance consists of 29 moving motifs, 6 moving phrases, 2 moving sentences, and 1 moving cluster, which form a complete movement unit of the Ajaat Temuai Datai dance.